Reactive sulfur species as emerging immunomodulators: mechanistic insights and therapeutic prospects - Chen, Youbang; Ji, Ruiying; Wu, Yixing; Li, Xiang; Zhang, Hui; Yang, Chun-tao (Frontiers in Immunology, 2026)
Inflammation is a vital component of host defense and tissue repair, but its dysregulation contributes to chronic metabolic and immune-mediated diseases. In recent years, reactive sulfur species (RSS) have emerged as crucial regulators of immune homeostasis. Unlike reactive oxygen and nitrogen species, RSS dynamically regulates cellular signaling networks through reversible protein persulfidation. Rather than exerting uniformly pro- or anti-inflammatory actions, RSS display context-dependent, bidirectional effects that fine-tune immune responses according to the cellular redox state, metabolic and inflammatory conditions. This review integrates current advances in understanding how RSS mediate immune regulation across both innate and adaptive systems. We discuss how RSS shape macrophage polarization, modulate neutrophil activation and NETosis, influence dendritic cell differentiation, and control T and B cell function. We further examine translational efforts employing diverse RSS donors, including H2S-releasing compounds, persulfide and polysulfide donors, and engineered biomaterial delivery systems, to achieve targeted immune modulation. Finally, we highlight key challenges, such as context specificity, donor controllability, and redox balance, that must be resolved to realize the therapeutic potential of RSS.